ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NERACA PEMBAYARAN DI INDONESIA TAHUN 1986-2016 - Genta Noer Kahar; Indra Suhendra; Umayatu Suiroh Suharto (Jurnal Ekonomi-Qu, 2017)
This study aims to determine the effect of the Gross Domestic Product (GDP), Exchange Rate, External Debt (ULN) and Net Exports on the Balance of Payments in Indonesia. The data used in this study is annual data which began from 1986-2016. All data in this study were obtained from Bank Indonesia. This study uses the Ordinary Least Square (OLS) method. Based on the results of the partial test (t-test), it shows that the Gross Domestic Product and Net Export variables have a significant effect on the Balance Sheet. However, the exchange rate and foreign debt do not have a significant effect on the balance of payments in Indonesia.